The prevalence of elevated liver enzymes level(ALT/AST) in epileptic children treated with valproic acid(VPA) - العنيد, نيرمين; مازن غالية; سعاد صقور (Latakia University Journal -Medical Sciences Series, 2024)
Background: Epilepsy is considered the most common neurological disorder affecting children. Valproic acid is the most commonly prescribed antiepileptic drug, and although it is a safe drug, it may cause some side effects, such as elevated transaminase levels. Objective: The research aims to study the prevalence of elevated liver enzymes (ALT, AST) in epileptic children treated with valproic acid. Materials and Methods: An observational descriptive study (cross-sectional) was conducted for the period one year (May 2023–May 2024) at Tishreen University Hospital in Lattakia-Syria. The study included 240 children. ALT, AST were performed on a peripheral venous blood sample .The study included two groups of patients: group I patients with normal AST values, whereas group II patients with high AST values. Results: The results showed that 1.3% of the study population had elevated AST values, while ALT values ​​were normal in all children. No statistically significant difference was observed with regard to age group, gender, and drug dose and the incidence of clinical side effects between the two research groups (Pv > 0.05), while the duration of treatment was longer in the second group, Pv = 0.0001. Conclusion: Valproic acid can be used as a liver-safe treatment in the management of epilepsy.